Biological Functions and Prognostic Value of Ferroptosis-Related Genes in Bladder Cancer - Yi, Kezhen; Liu, JingChong; Rong, Yuan; Wang, Cheng; Tang, Xuan; Zhang, XiaoPing; Xiong, Yunhe; Wang, Fubing (Frontiers in Molecular Biosciences, 2021)
Background Every year, nearly 170,000 people die from bladder cancer worldwide. A major problem after transurethral resection of bladder tumor is that 40%–80% of the tumors recur. Ferroptosis is a type of regulatory necrosis mediated by iron-catalyzed, excessive oxidation of polyunsaturated fatty acids. Increasing the sensitivity of tumor cells to ferroptosis is a potential treatment option for cancer. Establishing a diagnostic and prognostic model based on ferroptosis-related genes may provide guidance for the precise treatment of bladder cancer. Methods We downloaded mRNA data in Bladder Cancer from The Cancer Genome Atlas (TCGA) and analyzed differentially expressed genes (DEGs) based on and extract ferroptosis-related genes. We identified relevant pathways and annotate the functions of ferroptosis-related DEGs using Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis (KEGG) and Gene Ontology functions (GO). On the website of Search Tool for Retrieving Interacting Genes database (STRING), we downloaded the protein-protein interactions of DEGs, which were drawn by the Cytoscape software. Then the Cox regression analysis were performed so that the prognostic value of ferroptosis-related genes and survival time are combined to identify survival- and ferroptosis-related genes and establish a prognostic formula. Survival analysis and receiver operating characteristic curve (ROC) validation were then performed. Finally, risk curves and nomograms were generated for both groups to predict survival. Results Eight ferroptosis-related genes with prognostic value (ISCU, NFE2L2, MAFG, ZEB1, VDAC2, TXNIP, SCD, JDP2) were identified. With clinical data, we established a prognostic model to provide promising diagnostic and prognostic information of bladder cancer based on the eight ferroptosis-related genes. Conclusion This study found that the ferroptosis-related genes is associated with bladder cancer, which may serve as new target for the treatment of bladder cancer.